ОСОБЛИВОСТІ ПЕРЕКЛАДУ ТА ТЕНДЕНЦІЇ РОЗВИТКУ НІМЕЦЬКОЇ НАУКОВО-ТЕХНІЧНОЇ ТЕРМІНОЛОГІЇ (Zaporizhzhia Historical Review, 2021)
The article deals with characteristic of German scientific and technical terminology on word-building and semantic levels. The analysis helps to find actual tendencies of terminological word-building namely borrowings, abbreviation, terminologisation and determinologisation.